Comparative Study on Interface Elements, Thin-Layer Elements, and Contact Analysis Methods in the Analysis of High Concrete-Faced Rockfill Dams. (26th September 2013) - Qian, Xiao-xiang; Yuan, Hui-na; Li, Quan-ming; Zhang, Bing-yin
Abstract : This paper presents a study on the numerical performance of three contact simulation methods, namely, the interface element, thin-layer element, and contact analysis methods, through the analysis of the contact behavior between the concrete face slab and the dam body of a high concrete-faced rockfill dam named Tianshengqiao-I in China. To investigate the accuracy and limitations of each method, the simulation results are compared in terms of the dam deformation, contact stress along the interface, stresses in the concrete face slab, and separation of the concrete face slab from the cushion layer. In particular, the predicted dam deformation and slab separation are compared with the in-situ observation data to classify these methods according to their agreement with the in-situ observations. It is revealed that the interface element and thin-layer element methods have their limitations in predicting contact stress, slab separation, and stresses in the concrete face slab if a large slip occurs. The contact analysis method seems to be the best choice whether the separation is finite or not.